Mechanical behavior of hybrid jute/flax epoxy composite - Aung, Lwin Moe (2015)
In recent year, natural fiber becomes an environmental advantage due to the environmental alertness.The goal of current study was to investigate the mechanical behavior of hybrid jute/flax epoxy composite based on the tensile properties.The jute twill and flax plain weave were laminated to produce a range of ligt weight panels.Specimens were prepared by hand layup and tested at cross head displacement rate of 1,250 and 500mm/min.The tensile test indicate that Flax plain/Jute/flax plain offered higher Young's Modulus than Jute/Flas plain/Jute.